Trade liberalization and premature deindustrialization in Colombia - Mateo Hoyos López (Journal of Economic Structures, 2017)
This work analyzes the phenomenon of premature deindustrialization for Colombia and for other seven Latin American countries. Through a Koyck transformation model for the Colombian case, and a panel data fixed effects model for the complete sample of eight Latin American countries, this work documents that the fall in the average effective tariff in the region is the main economic explanation of the premature reduction in the manufacturing share. Also, it provides evidence that relates negative performance of manufacturing to foreign investment flows and to Dutch disease. On the other hand, taking into account the importance of manufacturing on productive sophistication and economic development, this work applies product space methodology in order to determine strategic manufacturing sectors for the establishment of a selective industrial policy for the Colombian case. As a result, the sectors that must be encouraged by the Colombian State are manufactured intermediate goods, mainly goods in the chemical industry.
Keywords: 330; Deindustrialization; Tariffs; Washington Consensus; Industrial policy; Structural transformation; Colombia; Latin America